DEVELOPMENT OF LINGUISTIC COMPETENCE OF FUTURE ENGLISH TEACHERS IN THE EDUCATIONAL PROCESS BASED ON SMART TECHNOLOGIES IN THE ERA OF DIGITAL TECHNOLOGIES AND INNOVATIONS - Fayzullayeva Dilnoza Ubaydulloyevna (Journals Park Publishing, 2023)
In this article, in the era of digital technologies and innovations, several methods of developing linguistic competences of future English language teachers based on smart technologies and effective teaching of English, modern educational technologies used in language and its learning are discussed. is conducted.
Keywords: Digital technology, innovative, technologies, methodology, modern world, pedagogical innovation.